Parenting Program in Growing Parents' Positive Parenting at PAUD Al-Ummah Deli Tua - Munisa Munisa (Budapest International Research and Critics University, 2020)
Parenting is the basis for the child to shape his/her personality. One of the impacts of parenting will be seen when the child is in the school environment. Children's problems at school cannot be removed from parenting at home. The success of children in both academic and non-academic schools is also supported by the pattern of parenting that children receive in the family environment. Therefore, the education carried out in the school should synergize with the education carried out in the family. Parenting behavior towards the child often shows impatience, incapable of self-control, complaining when facing parenting difficulties and not listening to the child's problems attentively. This devotion aims to know the effectiveness of programs to positively improve parenting skills through Mindful parenting programs. Mindful parenting can be interpreted as parental awareness in paying attention, aiming and not labeling or negative assessment of each child's experience. Based on the above, it is necessary to do activities to address the problem through the devotion of parenting programs in fostering positive parenting behavior in Paud Al Ummah delitua.